Moonlight - Waldstein - Storm - Beethoven, Ludwig van 1770-1827; Lubimov, Alexei 1944- (Paris Cité de la musique Alpha, 2013)
Among Ludwig van Beethoven's most popular piano sonatas are the Sonata No. 14 in C sharp minor, "Moonlight," the Sonata No. 21 in C major,"Waldstein," and the Sonata No. 17 in D minor, "The Storm" (also known as "The Tempest"). Because of their great familiarity and variety of moods, they are excellent choices for demonstrating how Beethoven's music sounded on an instrument of his time, such as the of the 1802 Erard pianoforte, of which a modern copy by Christopher Clarke is used in these period-style performances by Alexei Lubimov. Where one might expect power, smoothness, and a rich, rounded tone from a modern concert grand, the sound of this pianoforte is slightly muted in soft passages, clangorous at its loudest, and even a little buzzing in its overtones. Nowhere are these qualities more shocking than in the first movement of "Moonlight," where the music takes on a remote and antique quality, reminiscent perhaps of a cimbalom or harpsichord in certain notes. But if, after hearing this movement, the listener has acclimatized to the instrument's quirky sonorities (which are quite variable throughout the disc), then the album can be enjoyed as a masterly recital of Beethoven's music and the instrument's attractive possibilities. The hybrid SACD is well-protected by a hardcover book, which not only has informative liner notes but several full color photographs of the pianoforte.
Keywords: 19th Century (1801-1900); Keyboard music; Sonata; Piano; Historically informed performance; Vienna (Austria)